2017
DOI: 10.1002/ldr.2821
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the uptake and acquisition of potentially toxic elements in plants and health risks associated with the addition of fresh biowaste amendments to industrially contaminated soil

Abstract: Soil contamination by potentially toxic elements (PTEs), due to rapid industrialization and urbanization, is a serious environmental concern that has been threatening both the sustainability of various agroecosystems and human health. Efforts to investigate the bioavailability, transfer, and accumulation of PTEs in the soil–plant system and their possible health consequences have almost exclusively focused in the past studies. However, there is limited evidence for increased human exposure to PTEs through diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The increase in translocation of Cd to fruits was in agreement with the findings of Pinto et al (2004a, 2004b), while, in another study Pinto et al (2005) reported an increase in Cd translocation with organic matter amendment in sorghum. Similarly Yousaf et al (2017) also reported an increase in translocation of Cd by wheat plant with the application of fresh biowastes. The increase in translocation of Cd might be due to changes in soil pH, because it is a key factor affecting the mobility and bioavailability of Cd, which are negatively correlated with soil pH (Chaudri et al, 2007; Liu et al, 2015).…”
Section: Resultsmentioning
confidence: 82%
“…The increase in translocation of Cd to fruits was in agreement with the findings of Pinto et al (2004a, 2004b), while, in another study Pinto et al (2005) reported an increase in Cd translocation with organic matter amendment in sorghum. Similarly Yousaf et al (2017) also reported an increase in translocation of Cd by wheat plant with the application of fresh biowastes. The increase in translocation of Cd might be due to changes in soil pH, because it is a key factor affecting the mobility and bioavailability of Cd, which are negatively correlated with soil pH (Chaudri et al, 2007; Liu et al, 2015).…”
Section: Resultsmentioning
confidence: 82%
“…24,29 In addition, the lowest available Cd concentration in HS treatment is also attributed to its relatively high CEC and soil OC (Table 1), as a signicantly negative correlation between soil available Cd and CEC as well as OC was reported. 30,31 Similarly, electrostatic attraction also occurs between anions like Cd and the negatively charged surface of BC and its functional groups (e.g. phenol hydroxyl, carboxyl, and carbonyl groups).…”
Section: Resultsmentioning
confidence: 99%
“…The application of SPM and CM reduced the Cd uptake (Table 3) which protected the photosynthetic apparatus from the damaging effects of Cd [7,73], resulting in a significant increase in photosynthetic pigments (Table 1). Moreover, OA had beneficial impacts on soil characteristics, and improve root growth, nutrient and water uptake and reduce the Cd uptake (Table 3) which also favors a significant increase in the synthesis of photosynthetic pigments [74].…”
Section: Discussionmentioning
confidence: 99%